A comparison of outcomes for early oropharyngeal cancers treated with single-modality surgery versus radiotherapy. (July 2014) - Valakh, Vladimir; Miyamoto, Curtis; Mazurenka, Katsiaryna; Liu, Jeffrey C
Aims: We retrospectively compared results of surgery alone (SX) or radiotherapy alone (RT) for early stage tonsil and base of tongue cancers.Materials & methods: Outcomes for 386 SX and 362 RT patients from Surveillance, Epidemiology and End Results database were analyzed using propensity covariate adjusted and inverse probability weighting models.Results: With median follow-up of 71 months, unadjusted overall survival at 5 years was 66.1% for SX versus 50.2% for RT (p < 0.001). Unadjusted cancer-specific survival was 80.9% for SX versus 67.3% for RT (p < 0.001). In multivariate analysis, treatment modality maintained association with overall survival and cancer-specific survival. Inverse probability weighting-adjusted 5-year overall survival was 75.2% for SX versus 67.4% for RT (p = 0.002). Inverse probability weighting-adjusted cancer-specific survival was 86.0% for SX versus 77.4% for RT (p < 0.001).Conclusion: Explanations for higher survival for SX include comorbidities, superiority of surgery and underascertainment of postoperative radiation in Surveillance, Epidemiology and End Results.